AB0930 EFFICACY OF TOCILIZUMAB IN TREATMENT OF SYSTEMIC JUVENILE IDIOPATHIC ARTHRITIS IN PATIENTS WITH MACROPHAGE ACTIVATION SYNDROME. (June 2019) - Alexeeva, Ekaterina; Dvoryakovskaya, Tatyana; Isaeva, Ksenia; Denisova, Rina; Soloshenko, Margarita; Fetisova, Anna; Mamutova, Anna; Vankova, Dariya; Chomahidze, Alexandra; Kriulin, Ivan; Alshevskaya, Alina; Moskalev, Andrey
Abstract : Background: Macrophage activation syndrome (MAS) is a rare and severe complication of juvenile idiopathic arthritis (JIA) that most typically develops in patients with its systemic form (sJIA). Tocilizumab proved to be efficacious for treatment of both systemic JIA and polyarthritis. Nevertheless, the question regarding the effect of MAS on efficacy of TOC therapy in patients with sJIA is still to be solved. Objectives: To evaluate the efficacy of tocilizumab therapy in patients having sJIA and MAS versus the patients without MAS. Methods: Throughout the period between 2009 and 2018, 251 children with the acute phase of sJIA started to be treated with TOC at the Rheumatology Department of the National Medical Research Center of Children's Health (Moscow, Russia). Of those, 69 patients had active MAS at initiation of TOC therapy. Patients were diagnosed with MAS according to the preliminary diagnostic guidelines for MAS complicating sJIA [1]. Treatment efficacy was evaluated according to the dynamics of clinical and laboratory signs using the ACRPedi criteria. The Wallace criteria were used to evaluate whether or not remission had been achieved. Results: At initiation of TOC therapy, patients with and without MAS were comparable in terms of their sex and age characteristics, as well as the overall severity of arthritis (the percentage of women, 56.6% (intergroup p=0.396); the median age, 7.83 (4.39-11.3) years (intergroup p=0.640); and JADAS-71, 17.4 (13.7-22.8) (intergroup p=0.055)). Nevertheless, patients differed in terms of intensity of certain clinical manifestations and prior history of the disease. The group with MAS was characterized by such parameters as shorter disease duration, shorter duration morning stiffness, and smaller number of affected joints but higher activity and severity score (Patient/Parent and Physician VAS score). After treatment initiation, TOC was discontinued after treatment for 4-12 weeks only in 2 out of 69 (2.9%) patients because of persistent MAS or MAS flare. The patients successfully achieved remission after therapy switching. No intergroup differences were observed for the rate of treatment discontinuation within the first year of therapy: the drug was discontinued in 5 (7.2%) patients in the MAS+sJIA group (2 MAS flares + 3 cases of poor efficacy) and in 25 (13.7%) patients in the sJIA group (4 SAEs + 21 cases of poor efficacy). One-year treatment with TOC proved that this drug is highly efficacious to treat sJIA regardless of whether or not patients had MAS at treatment initiation (Figure). No deaths were reported throughout the entire treatment period. We attributed this to early diagnosis and high efficacy of treatment of JIA patients. Conclusion: Tocilizumab therapy in patients with sJIA in the presence of MAS is as efficacious as in patients without MAS and does not aggravate the course of MAS. Reference: [1] Ravelli A, Magni-Manzoni S, Pistorio A, Besana C, Foti T, Ruperto N, Viola S, Martini A. Preliminary diagnostic guidelines for macrophage activation syndrome complicating systemic juvenile idiopathic arthritis. J Pediatr. 2005;146(5):598-604. Disclosure of Interests: None declared